EKONOMISASI PEKARANGAN UMAT HINDU BERLANDASKAN TRI HITA KARANA - Ni Nyoman Satya Widari; Ni Putu Ari Aryawati (Department of Agricultural Social Economics Faculty of Agriculture University of Mataram, 2021)
This study aims to determine the perception of Hindus community in Mataram about the use of the yard, the form of the use of the yard and the implications of the use of the yard based on Tri Hita Karana philosophy . This study uses a descriptive qualitative approach by conducting direct observations, in-depth interviews and document studies. Description tell what happened and trying to get facts related to the use of yards by Hindus in Mataram City, West Nusa Tenggara. The results of this study stated that the perception of Hindus in the city of Mataram about the use of the landscape based on Tri Hita Karana is to create a balance which means the realization of harmony in life, especially between humans and their environment, which in Panca Yadnya means Bhuta Yadnya, which is addressed to the Bhuta Kala, namely the elements of nature. The form of utilization of the yard Hindus follow a cropping pattern called Caraka with the placement of plants in the yard according to their function in each family, namely as a provider of food, complementary to traditional ceremonies, medicinal ingredients and as a fulfillment of beauty. The implication of optimal use of the yard by Hindus also means participating in the palemahan principle, namely establishing a harmonious relationship with nature while reducing dependence on materials for daily needs that are purchased or imported from outside the city of Mataram.